Assuming Personal Responsibility for Sexual Victimization: Harmful But Potentially Adaptive for College Women? - Donde, Sapana D. (Journal of interpersonal violence, 2021)
Survivors of sexual trauma often experience pervasive adverse cognitive attributions, such as assuming responsibility for victimization. In fact, these negative outcomes were recently included in the Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5) criterion for posttraumatic stress disorder (PTSD) and have garnered substantial research attention devoted toward investigating the effectiveness of empirically supported trauma treatments in altering and reducing maladaptive belief systems. However, less is known about the ways that these negative cognitions may be inadvertently serving an adaptive role in young women’s healing and recovery from sexual trauma. The present study examined relationships between situational aspects of sexual victimization, personal responsibility, self-esteem, perceived future control, and perceived future likelihood of assault recurrence using path analysis in a sample of college women (n = 347) who had experienced sexual victimization. Increased physical harm, decreased intoxication of the male, increased survivor intoxication, and decreased clarity of nonconsent were associated with increased personal responsibility, which was positively associated with self-esteem and perceived future control. Self-esteem mediated a negative relationship between personal responsibility and perceived future likelihood of assault recurrence, while perceived future control mediated a positive relationship. Findings suggest that college women’s tendency to assume personal responsibility for sexual victimization experiences is a complicated double-edged sword with both harmful and adaptive effects. Innovative, comprehensive, and sophisticated approaches to sexual assault prevention and treatment are needed to more effectively address this issue and support young women’s healing and recovery from victimization.